Inhibition of Butyrylcholinesterase and Human Monoamine Oxidase-B by the Coumarin Glycyrol and Liquiritigenin Isolated from Glycyrrhiza uralensis - Geum Seok Jeong; Myung-Gyun Kang; Joon Yeop Lee; Sang Ryong Lee; Daeui Park; MyoungLae Cho; Hoon Kim (Molecules, 2020)
Eight compounds were isolated from the roots of Glycyrrhiza uralensis and tested for cholinesterase (ChE) and monoamine oxidase (MAO) inhibitory activities. The coumarin glycyrol (GC) effectively inhibited butyrylcholinesterase (BChE) and acetylcholinesterase (AChE) with IC50 values of 7.22 and 14.77 µM, respectively, and also moderately inhibited MAO-B (29.48 µM). Six of the other seven compounds only weakly inhibited AChE and BChE, whereas liquiritin apioside moderately inhibited AChE (IC50 = 36.68 µM). Liquiritigenin (LG) potently inhibited MAO-B (IC50 = 0.098 µM) and MAO-A (IC50 = 0.27 µM), and liquiritin, a glycoside of LG, weakly inhibited MAO-B (>40 µM). GC was a reversible, noncompetitive inhibitor of BChE with a Ki value of 4.47 µM, and LG was a reversible competitive inhibitor of MAO-B with a Ki value of 0.024 µM. Docking simulations showed that the binding affinity of GC for BChE (−7.8 kcal/mol) was greater than its affinity for AChE (−7.1 kcal/mol), and suggested that GC interacted with BChE at Thr284 and Val288 by hydrogen bonds (distances: 2.42 and 1.92 Å, respectively) beyond the ligand binding site of BChE, but that GC did not form hydrogen bond with AChE. The binding affinity of LG for MAO-B (−8.8 kcal/mol) was greater than its affinity for MAO-A (−7.9 kcal/mol). These findings suggest GC and LG should be considered promising compounds for the treatment of Alzheimer’s disease with multi-targeting activities.